1993
DOI: 10.1096/fasebj.7.6.8472896
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte expression of mRNA encoding cytokines IP‐10 and JE/MCP‐1 in experimental autoimmune encephalomyelitis

Abstract: Mononuclear leukocytes preferentially accumulate in the central nervous system (CNS) during the course of experimental autoimmune encephalomyelitis (EAE). To address factors that govern leukocyte trafficking in EAE, we monitored expression of mRNAs encoding IP-10 and JE/MCP-1, which are members of a family of chemoattractant cytokines. A transient burst of IP-10 and JE/MCP-1 mRNA accumulation in the CNS occurred, in close relation to the onset of histologic and clinical disease. In situ hybridizations showed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
290
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(313 citation statements)
references
References 0 publications
20
290
0
3
Order By: Relevance
“…[25][26][27] The enhanced expression of IP-10 and MIG in the type-1 response is in accord with the dominant role of IFN-␥ in this response. IP-10 expression is induced by IFN-␥ in endothelial cells, monocytes, fibroblasts, keratinocytes, 28,29 astrocytes, 30 and neutrophils. 31 MIG is expressed by IFN-␥-stimulated mononuclear cells, endothelial cells, keratinocytes, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] The enhanced expression of IP-10 and MIG in the type-1 response is in accord with the dominant role of IFN-␥ in this response. IP-10 expression is induced by IFN-␥ in endothelial cells, monocytes, fibroblasts, keratinocytes, 28,29 astrocytes, 30 and neutrophils. 31 MIG is expressed by IFN-␥-stimulated mononuclear cells, endothelial cells, keratinocytes, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IP-10 is an ELR-negative (i.e., contains no Glu-Leu-Arg motif) ␣ chemokine with known chemotactic effects on T cells and monocytes, as well as antiviral, anti-angiogenic, and anti-tumor properties (Luster and Leder, 1993;Angiolillo et al, 1995;Ben-Baruch et al, 1995). It is expressed in astrocytes in a number of different inflammatory, infectious, and degenerative conditions of the CNS (Ransohoff et al, 1993;Asensio and Campbell, 1999). The promoter regions for both of these chemokines contain several transcription regulatory elements, but analysis of the IL-8 promoter has shown that expression requires the activity of a combination of either NF-B and AP-1 or NF-B and NF-IL-6 (Mahe et al, 1991;Yasumoto et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inflammatory cytokines have been demonstrated in the CNS during active EAE (32)(33)(34), whereas recovery has been associated with concomitant decreased CNS expression of IFN-% IL-2, IL-4, and IL-6 and increased expression of IL-10 m R N A (35). Furthermore, bursts of m R N A expression for inflammatory chemokines occur immediately before the initiation of both EAE onset (36,37) and relapse (38) in SjL/j mice, whereas abrupt decreased expression often occurs during remission. However, perhaps the most convincing evidence to date for immune mediation of relapse are the results obtained from an IFN-~/clinical trial that produced a high enough rate of MS relapse to terminate treatment (39).…”
Section: Discussionmentioning
confidence: 99%